Pengaruh Intensitas Belajar, Interaksi Sosial, Gaya Belajar, Perhatian Orangtua dan Pemanfaatan Internet Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XI IPS di SMA N 1 Luhak Nan Duo Kabupaten Pasaman Barat - Hijrah Safitri; Desi Areva; Jimi Ronald (Horizon, 2023)
This study aims to analyze 1) the effect oflearning intensityon learning achievement, 2) influencesocial interactionson learning achievement, 3)learning styleon learning achievement, 4) influenceparents attentionon learning achievement, 5) influenceinternet usageat school on learning achievement, (6) the effect oflearning intensity, social interaction, learning style, parental attention and the use of the internet together for the economics learning party for class X1 IPS at SMA N 1 Luhak Nan Duo. This type of research is associative research. The population in this study were all social studies students in class X1 at SMA N 1 Luhak Nan Duo for the academic year 2021/2022, totaling 80 samples. Sampling using stratified random sampling technique. The instrument used for this research is a closed questionnaire using the Multilevel Linear Regression test and hypothesis testing with t test and F test. ResultsThe research shows that: (1) there is a significant effect between learning intensity on learning achievement with the value of the coefficient0.245,tcount3,112> t table of 1.99254; (2) there is a significant influence between social interaction on learning achievement with the value of the coefficient0.159, tcount2,130> t table of 1.99254; (3) there is a significant influence between learning style on learning achievement with the coefficient value0.184, tcount2,569> t table of 1.99254; (4) there is a significant influence between parental attention to student achievement with the coefficient value of0.188and the value of tcount is4,603> t table of 1.99254; (5) there is a significant influence between the use of the internet on student achievement with the coefficient value0.172and the value of tcount is2,829> t table of 1.99254; (6) there is an effect of learning intensity, social interaction, learning style, parental attention, and the use of the internet together on learning achievement with Fcount115.731>Ftable 2.49 and significant value 0.000 <0.05.Keywords: Learning achievement, Learning Intensity, Social interactions, Learning Style, Parents attention, Internet Utilization.